Phase-specific stable isotope fractionation effects during combined gas-liquid phase exchange and biodegradation. (15th September 2022) - Khan, Ali M.; Gharasoo, Mehdi; Wick, Lukas Y.; Thullner, Martin
Abstract: Stable isotope fractionation of toluene under dynamic phase exchange was studied aiming at ascertaining the effects of gas-liquid partitioning and biodegradation of toluene stable isotope composition in liquid-air phase exchange reactors (Laper). The liquid phase consisted of a mixture of aqueous minimal media, a known amount of a mixture of deuterated (toluene-d) and non-deuterated toluene (toluene-h), and bacteria of toluene degrading strain Pseudomonas putida KT2442. During biodegradation experiments, the liquid and air-phase concentrations of both toluene isotopologues were monitored to determine the observable stable isotope fractionation in each phase. The results show a strong fractionation in both phases with apparent enrichment factors beyond −800‰. An offset was observed between enrichment factors in the liquid and the gas phase with gas-phase values showing a stronger fractionation in the gas than in the liquid phase. Numerical simulation and parameter fitting routine was used to challenge hypotheses to explain the unexpected experimental data. The numerical results showed that either a very strong, yet unlikely, fractionation of the phase exchange process or a – so far unreported – direct consumption of gas phase compounds by aqueous phase microorganisms could explain the observed fractionation effects. The observed effect can be of relevance for the analysis of volatile contaminant biodegradation using stable isotope analysis in unsaturated subsurface compartments or other environmental compartment containing a gas and a liquid phase. Graphical abstract: Image 1 Highlights: VOC biodegradation leads to stable isotope fractionation in aqueous and gas phase. Isotope fractionation effects are stronger in gas phase than in aqueous phase. Results indicate strong phase exchange fractionation or gas-phase VOC degradation.